Ocena użyteczności metody jakościowej szacowania popytu na przewozy ładunków żeglugą śródlądową na zapleczu portów morskich - Filina-Dawidowicz, Ludmiła; Kotowska, Izabela; Mańkowska, Marta; Pluciński, Przemysław (Prace Komisji Geografii Komunikacji PTG, 2020)
Usability evaluation of the qualitative method of estimating the demand for inland shipping serving the seaport hinterland Known methods of forecasting the demand for goods transport are based on given time series, which are not always available. The article aims to assess the usefulness of the qualitative method of estimating the demand for cargo transport by inland waterways in seaports hinterland when historical data are unavailable. The assessed method consists of five stages and is based on a demand survey, which was carried out among cargo senders. The verification performed on the Oder Waterway example, analysing potential operations performed in inland shipping to/from seaports in Szczecin and Świnoujście, on the assumption that the Waterway has been modernized to navigability class III. Obtained research results allowed to determine the strengths and weaknesses of predicting using analysed qualitative method pointing to its usability and can be useful for seaports authorities, forwarders, transport companies and government institutions making decisions regarding the development of inland waterway infrastructure.